Surface porous catalytic material based on raised damascene steel as well as preparation method and application of surface porous catalytic material
By forming a double-region mesh porous structure on the surface of wavy Damascus steel, the problem of difficult to balance the catalytic activity and selectivity of existing porous metal catalytic materials when treating dye wastewater is solved, and the effect of efficient degradation of dye wastewater is achieved and the effect of ensuring that Mechanical properties and integrity of the material.
Patent Information
- Application Number
- CN202411359107.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
When existing porous metal catalytic materials treat dye wastewater, the catalytic activity and selectivity are difficult to balance, and the material is highly brittle, and it is easy to be crushed by dye solution, and the degradation efficiency is low.
Wavy Damascus steel is used as the matrix, and a double-region mesh porous structure is formed by dealloyment treatment, which improves catalytic activity and mechanical properties, ensures material integrity, and achieves efficient degradation of dye wastewater.
Through the dual-region mesh porous structure, the activity and degradation efficiency of the catalyst are improved, the degradation rate reaches 93.71%, and the mechanical properties and integrity of the material are ensured, achieving efficient degradation of dye wastewater.
Smart Images

Figure CN119237025A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous metal catalytic materials, and in particular to a surface porous catalytic material based on corrugated Damascus steel, and a preparation method and application thereof. Background Art
[0002] Dye wastewater is one of the most difficult industrial wastewaters and environmental toxins to treat. Its discharge will cause serious pollution to water bodies and soil. Most of the dyes are highly toxic, dark in color, high in organic matter content, and difficult to degrade. When they are discharged into water bodies, they will cause serious pollution to the environment and endanger human health. Traditional treatment methods, such as physical adsorption, microbial degradation, and chemical oxidants, are complex, time-consuming, and labor-intensive to treat these dye wastewaters. They cannot be completely degraded and will also cause secondary pollution to the water body.
[0003] Porous metal catalytic materials, because of their large number of pore structures on the surface, can provide a large specific surface area, thereby significantly enhancing the contact between the catalyst and the reactants and improving the activity of the catalyst. Porous metal catalytic materials have attracted widespread attention due to their excellent performance in catalytic reactions.
[0004] Iron-based single-stage porous materials are typical porous metal catalytic materials, which have a three-dimensional bicontinuous nanopore metal structure. The catalytic activity can be improved by the continuous nanopore structure. However, due to the single pore size, it is impossible to achieve a balance between the activity of the catalyst and the selectivity for the target product. For complex wastewater systems such as dye wastewater, the catalytic effect is not satisfactory.
[0005] The iron-based two-stage porous structure establishes secondary pores on the ligaments of the single-stage porous structure. Through the two-stage pores, the specific surface area is further increased, the catalytic efficiency is improved, and to a certain extent, the activity of the catalyst and the selectivity for the target product are balanced. However, generally, the pore sizes of this two-stage porous structure are too different. Due to the influence of the surface tension of the catalytic medium, the secondary porous structure cannot effectively degrade the dye solution, which ultimately limits the improvement of the degradation efficiency in the entire catalytic process.
[0006] Conventional porous metal catalytic materials are mostly strip materials with a thickness of microns. The surface stress will cause stress concentration, resulting in the material being brittle and easy to break into pieces. In actual application, it is easy to be broken by the dye solution, resulting in reduced degradation efficiency or even inability to degrade further. Summary of the invention
[0007] The purpose of the present invention is to provide a surface porous catalytic material based on corrugated Damascus steel and a preparation method thereof in view of the deficiencies in the prior art. Corrugated Damascus steel is used as a substrate, and a dual-region network porous structure is obtained by dealloying to improve the catalytic activity and more effectively degrade dye molecules.
[0008] According to a first aspect of the present invention, a surface porous catalytic material based on corrugated Damascus steel is provided. The catalytic material uses corrugated Damascus steel as a matrix, wherein the matrix includes a first region and a second region, wherein the first region and the second region are alternately distributed to form corrugations;
[0009] Forming irregular first channels on the surface of the first region by dealloying the matrix, wherein the first channels are connected to the surface of the first region through first ligaments to form a single-layer mesh porous structure, and an average width of the first channels is greater than an average width of the first ligaments; and
[0010] Multiple layers of irregular second channels are formed on the surface of the second region. The second channels are connected to the surface of the second region through second ligaments to form a multi-layer mesh porous structure interlaced with each other. The average width of the second channels is greater than the average width of the second ligaments.
[0011] As an optional embodiment, the average width of the first channel is 0.14 μm to 1.59 μm, and the average width of the first ligament is 100 nm to 440 nm.
[0012] As an optional embodiment, the average width of the second channel is 0.1 μm to 1.49 μm, and the average width of the second ligament is 140 nm to 480 nm.
[0013] As an optional embodiment, the composition of the first region, calculated by mass fraction, includes: C≤0.08%, Mn≤2.00%, P≤0.045%, S≤0.030%, Si≤1.00%, Cr: 18.00%~20.00%, Ni: 8.0%~11.0%, and the rest is Fe.
[0014] As an optional embodiment, the composition of the second region, calculated by mass fraction, includes: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe.
[0015] As an optional implementation, the thickness of the substrate is 1 mm to 20 mm.
[0016] According to a second aspect of the present invention, there is provided a method for preparing the aforementioned surface porous catalytic material based on corrugated Damascus steel, comprising:
[0017] The pretreated corrugated Damascus steel is placed in an acid solution for dealloying, and after the dealloying is completed, it is washed with deionized water until it is neutral, and dried at room temperature to obtain a surface porous catalytic material;
[0018] The wavy Damascus steel has first and second regions that are alternately distributed, and the first and second regions are alternately distributed to form wavy patterns;
[0019] The composition of the first region, calculated by mass fraction, includes: C≤0.08%, Mn≤2.00%, P≤0.045%, S≤0.030%, Si≤1.00%, Cr: 18.00% to 20.00%, Ni: 8.0% to 11.0%, and the rest is Fe;
[0020] The components of the second region, calculated by mass fraction, include: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe.
[0021] As an optional implementation, hydrochloric acid with a pH value less than 7 is used for dealloying, and the dealloying time is 48 hours to 168 hours.
[0022] According to a third aspect of the present invention, there is provided a multi-stage pipeline continuous degradation reaction device, comprising a plurality of interconnected pipelines, each stage of the pipeline is provided with a controller for controlling the rotation of the rotor blades, and a water inlet is provided on the first stage of the pipeline, and a water outlet is provided on the last stage of the pipeline;
[0023] Among them, each stage of the pipeline is equipped with multiple groups of series-connected rotor blades, and the material of the rotor blades is the aforementioned surface porous catalytic material based on corrugated Damascus steel.
[0024] According to a fourth aspect of the present invention, there is provided a degradation method for treating dye wastewater using the aforementioned multi-stage pipeline continuous degradation reaction device.
[0025] It can be seen from the above technical scheme of the present invention that the surface porous catalytic material based on corrugated Damascus steel proposed by the present invention improves the degradation regional activity of dye molecules through the regional distribution of porous structure, and forms a dual-region mesh porous structure through dealloying. The surface of the first region has a single-layer mesh structure formed by large channels, and the pollutant molecules are quickly transmitted and diffused to the adjacent second region through the large channels of the first region, thereby improving the catalytic efficiency; the second region has a multi-layer mesh structure, which is interlaced to form a fine pore structure with a higher specific surface area, providing more active sites, so that the pollutant molecules are fully in contact with it, thereby improving the degradation efficiency, and the alternating first region and second region ensure that all pollutant molecules are in complete contact with the catalytic material, thereby achieving the purpose of efficiently degrading dye wastewater, and the degradation rate is as high as 93.71%.
[0026] The surface porous catalytic material of the present invention has a certain thickness and is porous treated on the surface, has excellent mechanical properties, and can ensure the integrity of the material itself during the entire treatment process, thereby ensuring smooth degradation and having high degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a picture of an exemplary wavy Damascus steel matrix.
[0028] Figure 2 It is a structural schematic diagram of a multi-stage pipeline continuous degradation reaction device in an example of the present invention.
[0029] Figure 3 3a is a macroscopic metallographic image of the wavy Damascus steel substrate before treatment; 3b is a macroscopic SEM image of the material after treatment; 3c is a 2000 times SEM image of region A after treatment; 3d is a 20000 times SEM image of region A after treatment; 3e is a 2000 times SEM image of region B after treatment; 3f is a 20000 times SEM image of region B after treatment.
[0030] Figure 4 This is an ultraviolet spectrum of the material of Example 1 of the present invention that degrades methyl into dye. DETAILED DESCRIPTION
[0031] In order to better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.
[0032] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.
[0033] Wavy Damascus steel is formed by combining two or more materials with different properties through carburizing, repeated folding and forging. By controlling different folding methods and forging techniques, different microstructure patterns with certain periodic characteristic structures are presented, such as Figure 1 As shown. Damascus steel has the advantages of high strength, hardness and good toughness.
[0034] Based on this, the present invention adopts wavy Damascus steel as the base material, and obtains a dual-region mesh porous structure on the base by dealloying.
[0035] Surface porous catalytic materials based on corrugated Damascus steel
[0036] In an exemplary embodiment of the present invention, a surface porous catalytic material based on corrugated Damascus steel is provided. The catalytic material uses corrugated Damascus steel as a matrix, and the matrix includes a first region and a second region, and the first region and the second region are alternately distributed to form corrugations.
[0037] Forming irregular first channels on the surface of the first region by dealloying the matrix, the first channels being connected to the surface of the first region through first ligaments to form a single-layer mesh porous structure, and the average width of the first channels is greater than the average width of the first ligaments; and
[0038] Multiple layers of irregular second channels are formed on the surface of the second region. The second channels are connected by second ligaments to form a mutually staggered multiple layers of mesh porous structure on the surface of the second region. The average width of the second channels is greater than the average width of the second ligaments.
[0039] As an optional example, the average width of the first channel is 0.14 μm to 1.59 μm, and the average width of the first ligament is 100 nm to 440 nm.
[0040] As an optional example, the average width of the second channel is 0.1 μm to 1.49 μm, and the average width of the second ligament is 140 nm to 480 nm.
[0041] As an optional example, the composition of the first region, calculated by mass fraction, includes: C≤0.08%, Mn≤2.00%, P≤0.045%, S≤0.030%, Si≤1.00%, Cr: 18.00%~20.00%, Ni: 8.0%~11.0%, and the rest is Fe.
[0042] In a specific example, the first region is 06Cr19Ni10.
[0043] As an optional example, the composition of the second region, by mass fraction, includes: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe.
[0044] In a specific example, the second region is 20Cr13.
[0045] As an optional example, the thickness of the substrate is 1 mm to 20 mm. The thicker substrate ensures that the porous material has excellent mechanical properties and can ensure the integrity of the material itself during the entire processing process, thereby ensuring smooth degradation and high degradation efficiency.
[0046] It can be understood that the thickness of the substrate includes but is not limited to the above range of values, and can be selected according to needs. The substrate can even have a non-uniform thickness according to needs.
[0047] Preparation method of surface porous catalytic material based on corrugated Damascus steel
[0048] In another exemplary embodiment of the present invention, a method for preparing the aforementioned surface porous catalytic material based on corrugated Damascus steel is provided, comprising:
[0049] The pretreated corrugated Damascus steel is placed in an acid solution for dealloying. After the dealloying is completed, it is washed with deionized water to neutrality and dried at room temperature to obtain a surface porous catalytic material.
[0050] The wavy Damascus steel has first and second regions that are alternately distributed, and the first and second regions are alternately distributed to form wavy patterns;
[0051] The composition of the first region, by mass fraction, includes: C≤0.08%, Mn≤2.00%, P≤0.045%, S≤0.030%, Si≤1.00%, Cr: 18.00% to 20.00%, Ni: 8.0% to 11.0%, and the rest is Fe;
[0052] The components of the second region, by mass fraction, include: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe.
[0053] In the aforementioned component system, the first region has higher contents of Cr and Ni elements than the second region, resulting in a larger potential difference between the first region and the second region. When the wavy Damascus steel is in an HCl solution, microgalvanic corrosion is formed between the first region and the second region, generating a microgalvanic corrosion current, which increases the dissolution rate of the second region (anode) with a lower potential, and causes a hydrogen evolution reaction in the first region (cathode) with a higher potential. As the active substances in the second region decrease, they are converted into a new anode region, thereby causing an anodic dissolution reaction in the first region. The alternating conversion of the dissolution regions forms two different reticular porous structures.
[0054] In a specific example, the wavy Damascus steel used as the substrate can be purchased directly. The pretreatment process generally involves removing surface impurities and oil stains, then removing the surface oxide layer, polishing to remove grinding scratches, and then drying for use.
[0055] As an optional example, hydrochloric acid with a pH value less than 7 is used for dealloying, and the dealloying time is 48 hours to 168 hours.
[0056] Application of surface porous catalytic materials based on corrugated Damascus steel
[0057] like Figure 2 As shown, in another exemplary embodiment of the present invention, a multi-stage pipeline continuous degradation reaction device is provided, comprising a plurality of interconnected pipelines 10.
[0058] Therein, a plurality of sets of rotating blades 11 connected in series are arranged in the pipeline 10, and the material of the rotating blades 11 is the aforementioned surface porous catalytic material based on corrugated Damascus steel.
[0059] As an example, the corrugated Damascus steel base material can be directly forged into a rotor blade shape, and then processed using the aforementioned method to obtain a dual-zone mesh porous structure on the base, which can be directly used as a rotor blade of a multi-stage pipeline continuous degradation reaction device.
[0060] Each stage of the pipeline is equipped with a controller 12 for controlling the rotation of the impeller, and a water inlet 13 is provided on the first stage of the pipeline, and a water outlet 14 is provided on the last stage of the pipeline.
[0061] When treating sewage, the rotor blades 11 in each level of the pipeline are first started, and then the sewage to be degraded enters the first-level pipeline through the water inlet 13, flows into the second-level pipeline for rotor blade catalytic treatment after being catalytically treated by the rotor blades 11, and then enters the third pipeline for catalytic treatment in turn, until it flows out from the water outlet 14 after being treated in the last level of the pipeline, thus completing the entire treatment process.
[0062] As an optional example, the diameter of the pipeline 10 can be set to decrease step by step from the first stage to the last stage, so that the size of the impellers in the corresponding pipeline also decreases step by step, but the wastewater flow rate will increase, thereby improving the reaction efficiency and accelerating the degradation rate, while reducing costs and being more suitable for industrial applications.
[0063] It is understandable that during the entire degradation process, the reaction conditions can be adjusted according to actual conditions, or subsequent treatment can be performed; for example, electrochemical treatment can be combined in a multi-stage pipeline continuous degradation reaction device.
[0064] In the embodiments of the present invention, in view of the demand for rapid degradation treatment of dye wastewater, combined with the design of the aforementioned multi-stage pipeline continuous degradation reaction device, a rotary vane (i.e., a rotary blade) is configured as a degradation catalytic material, which can be driven to rotate. During the rotation process, the rapid degradation process of the dye wastewater is accelerated and promoted. Compared with the static catalytic material, the catalytic efficiency is improved by more than 50%. However, higher requirements are placed on the strength and wear resistance of the rotary vane as the catalytic material. The surface porous catalytic material of the corrugated Damascus steel proposed by the present invention, on the one hand, uses the corrugated Damascus steel as a substrate, has the advantages of high strength, high hardness and good toughness, and on the other hand, by The surface porous catalytic structure formed by the surface dealloying process, that is, the single-layer mesh porous structure and the interlaced multi-layer mesh porous structure formed in the alternating areas of the wavy Damascus steel surface, combined with the rotating action of the rotary blades, allows the polluted wastewater to quickly pass through the mesh porous structure of the alternating first area and the second area, which not only improves the rapid diffusion speed and efficiency of the polluted wastewater, but also provides more and denser catalytic sites, so that the pollutant molecules in the wastewater are fully combined and catalyzed by the active sites, thereby improving the degradation efficiency. Through the alternating degradation action, the catalytic decomposition efficiency and effect of the pollutant molecules are further guaranteed. The catalytic effect of 4 hours reaches more than 93%, achieving the purpose of efficient decomposition and catalysis.
[0065] At the same time, through the catalytic decomposition test, in the rotor blade structure of the embodiment of the present invention, after 4 hours of continuous rotation and catalytic decomposition, the rotor blade structure and the surface porous catalytic material layer remained intact and the morphology was basically unchanged, ensuring the long-term service life and degradation effect.
[0066] As an example, in one of the embodiments, a degradation method for treating dye wastewater using the aforementioned multi-stage pipeline continuous degradation reaction device is provided, comprising: in each stage of the multi-stage pipeline continuous degradation reaction device, or in any stage of the pipeline, using the aforementioned surface porous catalytic material based on corrugated Damascus steel as a working electrode, Pt as a counter electrode, and Ag / AgCl saturated electrode as a reference electrode in a three-electrode electrochemical system, using dye wastewater as an electrolyte, and degrading the dye wastewater using a cyclic square wave mode at 40°C.
[0067] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.
[0068] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.
[0069] The corrugated Damascus steel used in the embodiment is made of two steels with different compositions, wherein the A region is 06Cr19Ni10 and the rest is Fe, and its composition (mass fraction, wt%) is as follows:
[0070] element C Mn P S Si Cr Ni Content / wt% ≤0.08 ≤2.00 ≤0.045 ≤0.030 ≤1.00 18.00-20.00 8.0-11.0
[0071] The B area is 20Cr13, and the rest is Fe. Its composition (mass fraction, wt%) is as follows:
[0072] element C Mn Si Cr Ni P S Content / wt% 0.16-0.25 ≤1.00 ≤1.00 12.00-14.00 ≤0.75 ≤0.04 ≤0.03
[0073] Example 1
[0074] Use alcohol solution to remove impurities and oil stains on the surface of 12×10×3mm wavy Damascus steel, and then polish it one by one with sandpaper of roughness 80, 240, 400, 600, 800, 1000, 1200, 1500, 2000, and 3000. When using 80# sandpaper for polishing, make sure to remove the oxide layer on the surface of the sample.
[0075] After the wavy Damascus steel is polished, it is polished on a polishing machine with the help of a polishing cloth and silica polishing liquid. After the scratches during polishing are eliminated, anhydrous ethanol is used for ultrasonic treatment for 10 minutes to remove impurities on the surface.
[0076] The pretreated rose-grain Damascus steel was placed in a 0.1 mol / L hydrochloric acid solution for surface pickling for 168 hours to obtain a surface porous catalytic material.
[0077] Example 2
[0078] [SEM]
[0079] The surface porous catalytic material of Example 1 was subjected to SEM test. The results are as follows: Figure 3 shown.
[0080] Figure 3 a is a macroscopic image of the matrix material, where wavy patterns can be seen, with the light-colored area being marked as area A and the dark-colored area being marked as area B.
[0081] Figure 3 b is the macroscopic SEM image of the material after matrix treatment. It can be seen from the figure that the wavy pattern is not destroyed, and the material still has two regions A and B, which are distributed alternately with each other.
[0082] Figure 3 c and 3d are high-magnification images of area A and area B in 3b, respectively. It can be seen from the figures that the surface of area A is distributed with irregular channels, forming a single-layer mesh porous structure, while the surface of area B is distributed with multiple layers of irregular channels, forming an interlaced multi-layer mesh porous structure. At the same time, the average width of the channels in the two areas is greater than the average width of the ligaments in their respective areas.
[0083] According to the statistics of SEM images, the average width of the channels in region A is 0.14μm~1.59μm, and the average width of the ligaments in region A is 100nm~440nm; the average width of the channels in region B is 0.1μm~1.49μm, and the average width of the ligaments in region B is 140nm~480nm.
[0084] From the above, it can be seen that the present invention successfully prepared a surface porous catalytic material based on corrugated Damascus steel.
[0085] Example 3
[0086] [Catalytic performance]
[0087] Test sample (Porous 40°C): simulated wastewater, i.e., methyl orange solution with a concentration of 20 mg / L, was used as the degradable wastewater, and a multi-stage pipeline continuous degradation reaction device was used for degradation (in this test, there were three pipelines, and each pipeline was equipped with multiple sets of rotor blades, and the rotor blades were materials obtained by the method of Example 1). Then, in the first pipeline, the surface porous catalytic material obtained in Example 1 was used as the working electrode, Pt was used as the counter electrode, and Ag / AgCl (saturated) electrode was used as the reference electrode to form a three-electrode electrochemical system, and 50 mL of 20 mg / L methyl orange solution was used as the electrolyte. The electrolyte was treated in a water bath at 40°C using a cyclic square wave mode (the upper potential of the square wave was +1.5 V, the lower potential was -1.5 V, the holding time was 60 s, and the number of cycles was 120 times). After 240 minutes, a sample was taken from the water outlet, the solid and liquid were separated by a centrifuge, and the supernatant was taken, and the light absorption performance of the sample was tested by an ultraviolet spectrophotometer.
[0088] After the degradation was completed, after 4 hours of continuous rotation catalytic decomposition, the structure of the Damascus steel body as the matrix and the structure and morphology of the porous catalytic material on the surface of the test sample remained basically unchanged, maintaining a high degree of integrity.
[0089] Comparative sample 1 (Original 25°C) is different from the test sample in that the unde-alloyed wavy Damascus steel (pretreatment completed) is used as the working electrode and the degradation is carried out at 25°C.
[0090] Comparative sample 2 (Porous 25°C) is treated differently from the test sample in that the degradation is carried out at 25°C.
[0091] from Figure 4 It can be seen that by examining the absorbance at 465 nm, the degradation rate is calculated according to formula (1):
[0092]
[0093] Where A0 is the initial absorbance value of methyl orange, and A is the absorbance value of methyl orange after degradation.
[0094] According to the above formula, it is calculated that the degradation efficiency of the test sample is 93.71%, the degradation rate of the comparative sample 1 is 27.71%, and the degradation rate of the comparative sample 2 is 55.36%.
[0095] It can be seen that by using the catalytic material of the present invention to degrade the methyl orange solution, the methyl orange molecules can be efficiently degraded.
[0096] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A surface porous catalytic material based on corrugated Damascus steel, characterized in that: The catalytic material uses wavy Damascus steel as a matrix, the matrix includes a first region and a second region, the first region and the second region are alternately distributed to form wavy patterns; wherein irregular first channels are formed on the surface of the first region by dealloying the matrix, the first channels are connected to the surface of the first region through first ligaments to form a single-layer mesh porous structure, and the average width of the first channels is greater than the average width of the first ligaments; and Multiple layers of irregular second channels are formed on the surface of the second region. The second channels are connected to the surface of the second region through second ligaments to form a multi-layer mesh porous structure interlaced with each other. The average width of the second channels is greater than the average width of the second ligaments.
2. The surface porous catalytic material based on corrugated Damascus steel according to claim 1, characterized in that: The average width of the first channel is 0.14 μm to 1.59 μm, and the average width of the first ligament is 100 nm to 440 nm.
3. The surface porous catalytic material based on corrugated Damascus steel according to claim 1, characterized in that: The average width of the second channel is 0.1 μm to 1.49 μm, and the average width of the second ligament is 140 nm to 480 nm.
4. The surface porous catalytic material based on corrugated Damascus steel according to claim 1, characterized in that: The composition of the first region, calculated by mass fraction, includes: C≤0.08%, Mn≤2.00%, P≤0.045%, S≤0.030%, Si≤1.00%, Cr: 18.00% to 20.00%, Ni: 8.0% to 11.0%, and the rest is Fe.
5. The surface porous catalytic material based on corrugated Damascus steel according to claim 1, characterized in that: The components of the second region, calculated by mass fraction, include: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe.
6. The surface porous catalytic material based on corrugated Damascus steel according to claim 1, characterized in that: The thickness of the substrate is 1 mm to 20 mm.
7. A method for preparing a surface porous catalytic material based on corrugated Damascus steel according to any one of claims 1 to 6, characterized in that: include: The pretreated corrugated Damascus steel is placed in an acid solution for dealloying, and after the dealloying is completed, it is washed with deionized water until it is neutral, and dried at room temperature to obtain a surface porous catalytic material; The wavy Damascus steel has first and second regions that are alternately distributed, and the first and second regions are alternately distributed to form wavy patterns; The composition of the first region, calculated by mass fraction, includes: C≤0.08%, Mn≤2.00%, P≤0.045%, S≤0.030%, Si≤1.00%, Cr: 18.00% to 20.00%, Ni: 8.0% to 11.0%, and the rest is Fe; The components of the second region, calculated by mass fraction, include: C: 0.16% to 0.25%, Mn≤1.00%, Si≤1.00%, Cr: 12.00% to 14.00%, Ni≤0.75%, P≤0.04%, S≤0.03%, and the rest is Fe.
8. The preparation method according to claim 7, characterized in that: The dealloying treatment is carried out using hydrochloric acid with a pH value less than 7, and the dealloying time is 48 hours to 168 hours.
9. A multi-stage pipeline continuous degradation reaction device, characterized in that: It comprises a plurality of interconnected pipes (10), each stage of the pipes is provided with a controller (12) for controlling the rotation of the impellers, and a water inlet (13) is provided on the first stage of the pipe, and a water outlet (14) is provided on the last stage of the pipe; Wherein, a plurality of sets of rotating blades (11) connected in series are arranged in each stage of the pipeline, and the material of the rotating blades (11) is the surface porous catalytic material based on corrugated Damascus steel as described in any one of claims 1 to 6.
10. A degradation method for treating dye wastewater using the multi-stage pipeline continuous degradation reaction device according to claim 9.
